2010
DOI: 10.1007/s12289-010-0965-z
|View full text |Cite
|
Sign up to set email alerts
|

Study on the dry electrical discharge machining

Abstract: The dry electrical discharge machining is considered by the researchers as an environment friendly machining process and different specific aspects of this machining method are presented in the specialty literature. To obtain holes by electrical discharge machining, tubular rotating electrodes tools could be used. The paper presents a relatively simple device proposed to be used for applying the dry electrical discharge drilling. The rotation of the electrode tool could contribute to the diminishing of the err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 7 publications
0
11
0
2
Order By: Relevance
“…Deneyler 3'er tekrarlı yapılmış ve her delikten 3'er ölçüm alınarak ortalamaları performans değerleri olarak kullanılmıştır. Tüm deneylerde sabit sıcaklıkta (22 o C) dielektrik su soğutma sıvısı olarak kullanılmıştır. Bu çalışmada elektro erozyon parametreleri; akım (I), ark süresi (T on ) ark bekleme süresi (T off ), ve kapasitans (C) değerlerinin seçiminde Eyercioglu ve arkadaşlarının [26] …”
Section: Deneysel çAlişma (Experimental Study)unclassified
“…Deneyler 3'er tekrarlı yapılmış ve her delikten 3'er ölçüm alınarak ortalamaları performans değerleri olarak kullanılmıştır. Tüm deneylerde sabit sıcaklıkta (22 o C) dielektrik su soğutma sıvısı olarak kullanılmıştır. Bu çalışmada elektro erozyon parametreleri; akım (I), ark süresi (T on ) ark bekleme süresi (T off ), ve kapasitans (C) değerlerinin seçiminde Eyercioglu ve arkadaşlarının [26] …”
Section: Deneysel çAlişma (Experimental Study)unclassified
“…Results indicated that, open voltage, pulse duration, the amplitude of ultrasonic actuation, the discharge current, and the lessening of the wall thickness of electrode pipe are the significant factor for increasing the material removal rate. Besliu et al [12] studied dry EDM and performed experiments using liquid as well as the compressed air dielectric. Results showed that in the dry EDM process, electrode tool wear is better than wet EDM during particular operating conditions.…”
Section: Metal Removal Rate and Tool Wear Ratementioning
confidence: 99%
“…Results showed surface finish improved from 44μ Ra to 36μ Ra. Besliu et al [12] studied dry electrical discharge machining and find that the errors of the circular shape in a cross section through the hole may be reduced by rotation of the electrode tool. 3.3 Surface Integrity and Modeling Techniques Domenico Umbrello [34] performed experiments to analyze formations of white layers during machining of hardened AISI 52100 steel under dry and cryogenic cooling conditions.…”
Section: Polarity Overcut and Surface Roughnessmentioning
confidence: 99%
See 2 more Smart Citations